2002
DOI: 10.1037/1076-8998.7.4.313
|View full text |Cite
|
Sign up to set email alerts
|

Interactive training versus reading to teach respiratory protection.

Abstract: A tenet of behavioral education is that interactive training produces superior retention compared with reading. However, this has not often been directly tested and never with practical occupational information in working adults. Adults from diverse occupational backgrounds learned the principles of proper respiratory protection presented (a) in a book, (b) on a computer monitor, (c) through interactive computerized training consisting of textual information and illustrative pictures followed by quizzes and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 30 publications
2
33
2
Order By: Relevance
“…A moderately engaging, interactive training method such as CBT is presumably more effective than passive training (e.g., lectures) [39], and in the long term less costly than highly engaging methods (e.g., hands-on demonstrations) [46]. The current study suggests that even complex employee benefit information can be taught effectively using CBT.…”
Section: Discussionmentioning
confidence: 65%
“…A moderately engaging, interactive training method such as CBT is presumably more effective than passive training (e.g., lectures) [39], and in the long term less costly than highly engaging methods (e.g., hands-on demonstrations) [46]. The current study suggests that even complex employee benefit information can be taught effectively using CBT.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies of computer-based training have consistently shown that differences in how information is presented can have an effect on the learning (ChanLin, 1998;Eckerman et al, 2002;Hartley, 1994;Mayer, 2001;Wallen & Mulloy, 2005;Wallen, Plass, & Brunken, 2005). Research into instructional techniques to overcome working memory def icits has resulted in a number of instructional prescriptions described in cognitive load theory (Sweller & Chandler, 1991;Sweller, Chandler, Tierney, & Cooper, 1990).…”
Section: Agingmentioning
confidence: 97%
“…See Figure 1 for a summary of these comparisons. Interactive CBI Compared With Noninteractive CBI There were twenty comparisons that examined interactive CBI and noninteractive CBI (Bodemer, Ploetzner, Feuerlein, & Spada, 2004c1;Bodemer et al, 2004c2;Cook, Gelula, Dupras, & Schwartz, 2007;Darabi, Nelson, & Palanki, 2007;Davis, Bostow, & Heimisson, 2007;Dornisch & Sperling, 2006;Eckerman et al, 2002;Evans & Gibbons, 2007;Howard-Jones & Martin, 2002c1;Howard-Jones & Martin, 2002c2;Katayama & Crooks, 2003;Kerwin, 2006;Kritch & Bostow, 1998;Martin, Klein, & Sullivan, 2007;Miller & Malott, 1997c1;Miller & Malott, 1997c2;Moreno & Valdez, 2005c1;Rohlman et al, 2004c2;Tudor, 1995;Van Rooij, 2007 (Rohlman et al, 2004c1). In that study, interactive CBI was found to be superior to a manual with text-based quizzes and a manual without text-based quizzes.…”
Section: Comparisons Between Interactive Cbi and Another Instructionamentioning
confidence: 98%